Resposta Auditiva de Estado Estável: um estudo em crianças deficientes auditivas usuárias de amplificação - Bucuvic, Erika Cristina [UNIFESP] (2010)
Purpose: To evaluate auditory steady state response (ASSR) in free field in children with sensorineural hearing loss fitted with hearing aids and to compare the electrophysiological minimal response levels (LMR) to behavioral minimal response levels with and without amplification. Methods: Twenty-seven children were selected and divided into two groups: G1 consisted of 11 children aged eight to 43 months and G2 consisting of 16 children from 48 to 144 months of age. The evaluation included pure tone audiometry and ASSR in sound field with and without hearing aids. 500, 1000, 2000 and 4000 Hz frequencies were evaluated by means of frequency modulated tones (warble) for pure tones and ASSR was obtained using tone pips with modulation ratio varying from 77 to 103 Hz. As a measure of strenght of correlation was considered the correlation coeficient of Pearson, in each test case was set significance level of 0.05. Results: In the evaluation of 27 children, there was significant correlation between the behavioral NMRs and the ASSR at 1000 and 2000 Hz both obtained with hearing aids. Considering 500 and 4000 Hz, there was a tendency to significant correlation. In the analysis by age groups, there was a significant correlation in 1000 and 2000 Hz (0.66 and 0.70) for G1 and 2000 and 4000 Hz (0.56 and 0.62) for group G2. Mean differences between ASSR and behavioral minimal response levels varied from 7 to -22 dB and were not influenced by the degree of hearing loss.The shortest testing time was observed in the evaluation of profound hearing impaired children without hearing aids. Conclusion: It is possible to obtain the amplified NMRs using ASSR in free field with and without hearing aids with an average time of test of 53 minutes with amplification and 32.5 minutes without amplification. There is a correlation between electrophysiological responses and behavioral NMRs obtained with the use of amplification. The age is a source of variability in the correlation between the minimal response levels ASSR and behavioral and in the differences between the two procedures.